Análisis de los Impactos socioambientales producto del funcionamiento de la PTAR salitre. - Porras Vera, Luis Angel (Universidad Antonio Nariño, 2023)
Wastewater treatment plants (WWTP) are necessary buildings for environmental sustainability that are the alternative to the recovery of water bodies that a territory possesses and benefits human health, it must be taken into account that these plants can also generate impacts positive and negative on environmental and social aspects.